The Chapel of the Christ to the Column in the Toledo Cathedral: Some iconografic aftermaths of the altarpiece - Franco Mata, Ángela (Eikón / Imago, 2018)
In the cathedral of Toledo there is a chapel located in the ambulatory, which gives its name to the content, of special interest from the iconographic and theatrical point of view. It has an altarpiece with the representation of Christ tied to the column between St Peter and St John. It is the plastic interpretation of the Auto de la Pasión, by Alonso del Campo, written between 1486 and 1499. It is completed with the figure of Veronica. It had a certain diffusion in the field of miniature as in the Book of Hours of Alonso de Zúñiga, in the Royal Library of El Escorial, and in the sculpture, in the group of Christ to the column and St Peter (St John has been lost) in Alcaraz (Albacete).